Ultrasonic-Assisted tumbling improves water retention and tenderness of wooden breast chicken meat - Yanyan Lu; Zhenyang Wu; Tianjiao Bian; Xue Zhao (Ultrasonics Sonochemistry)
Wooden breast myopathy results in reduced meat tenderness, poor water retention, and diminished processing value, underscoring the urgency to mitigate economic losses caused by the deteriorated quality of wooden chicken breast. This study evaluated the effects of ultrasound-assisted tumbling (400 W, 20 kHz, 80 min) on the quality characteristics of wooden breast meat with varying severity levels, involving normal (NB), moderate (MB), and severe (SB) breast. Results showed that ultrasound-assisted tumbling treatment significantly decreased (P < 0.05) shear force by 29.88 ± 0.23 %, 22.07 ± 0.28 %, and 19.41 ± 0.22 % in NB, MB, and SB samples, respectively, while reducing cooking losses by 22.98 ± 0.07 %, 13.81 ± 1.10 %, and 9.91 ± 0.27 %. Additionally, ultrasound-assisted tumbling significantly increased salt-soluble protein content (P < 0.05) through optimized protein-water interactions, thereby improving water-binding capacity. Meanwhile, the low-field NMR indicated that the immobilized-water proportion of MB increased (95.25 ± 0.45 %). While total collagen decreased from 2.92 mg/g to 2.79 mg/g and soluble collagen from 0.75 mg/g to 0.72 mg/g, no significant change was observed in collagen solubility (P > 0.05). This work firstly reports successful application of ultrasound-assisted tumbling to effectively improve water-holding capacity and tenderness of wooden breast meat, achieving treated MB comparable quality metrics to untreated NB.